Endoplasmic reticulum stress improved chicken tenderness, promoted apoptosis and autophagy during postmortem ageing - Yuwei Chai; Lin Chen; Shuya Xiang; Linxuan Wu; Xuebo Liu; Jun Luo; Xianchao Feng (Food Science and Human Wellness)
In this study, endoplasmic reticulum (ER) stress inducer tunicamycin (TM) and inhibitor 4-phenylbutyric acid (4-PBA) were used to treat postmortem chicken breast muscle to investigate changes in tenderness and effects on apoptosis and autophagy during 5 days ageing. TM-induced ER stress reduced shear force, enhanced myofibril fragmentation index (MFI), disrupted myofibril structure, increased desmin degradation, and activated μ-calpain and caspase-12. In addition, TM-induced ER stress increased the expression of Bax, Bim, and cytochrome c, and decreased the expression of Bcl-xL. Furthermore, TM-induced ER stress improved the conversion of LC3I to LC3II, raised the expression of Beclin-1, and decreased the expression of p62, PI3K, and mTOR. The opposite results were observed after 4-PBA treatment. These results suggested that ER stress could improve chicken tenderness, promote apoptosis and autophagy during chicken postmortem ageing.